Slip and Hall Effects on Peristaltic Rheology of Copper-Water Nanomaterial Through Generalized Complaint Walls With Variable Viscosity - Awais, Muhammad; Kumam, Poom; Parveen, Nabeela; Ali, Aamir; Shah, Zahir; Thounthong, Phatiphat (Frontiers in Physics, 2020)
Current research is intended to examine the hydro-magnetic peristaltic flow of copper-water nanofluid configured in a symmetric three-dimensional rotating channel having generalized complaint boundaries incorporating second-order velocity slip conditions and temperature-dependent viscosity effects. Strong magnetic field with Hall properties, viscous dissipation, thermal radiations, and heat source/sink phenomenon have been studied. Constitutive partial differential equations are modeled and then simplified into a coupled system of ordinary differential equations by employing lubrication approximation. Consequential governing model is tackled numerically, and the results for flow quantities and Nusselt number are physically interpreted via graphs and bar charts toward the assorted parameters. Interpreted numerical results indicate that velocity components are accelerated with augmentation in first- and second-order velocity slip parameters and variable viscosity parameter, while it is reduced with a rise in Grashof number possessing dominant effects in the central region. Also, the temperature of the fluid increases with an increase in temperature-dependent viscosity effect.